Hybrid water adsorption and solubility partitioning for aerosol hygroscopicity and droplet growth - K. Gohil; C.-N. Mao; D. Rastogi; C. Peng; C. Peng; M. Tang; M. Tang; M. Tang; A. Asa-Awuku; A. Asa-Awuku (Atmospheric Chemistry and Physics, 2022)
In this work, we studied the cloud condensation nuclei (CCN) activity and subsaturated droplet growth of phthalic acid (PTA), isophthalic acid, (IPTA) and terephthalic acid (TPTA), significant benzene polycarboxylic acids and structural isomers found in the atmosphere. Köhler theory (KT) can be effectively applied for hygroscopicity analysis of PTA due to its higher aqueous solubility compared to IPTA and TPTA. As with other hygroscopicity studies of partially water-soluble and effectively water-insoluble species, the supersaturated and subsaturated hygroscopicity derived from KT principles do not agree. To address the disparities in the sub- and supersaturated droplet growth, we developed a new analytical framework called the Hybrid Activity Model (HAM). HAM incorporates the aqueous solubility of a solute within an adsorption-based activation framework. Frenkel–Halsey–Hill (FHH) adsorption theory (FHH-AT) was combined with the aqueous solubility of the compound to develop HAM. Analysis from HAM was validated using laboratory measurements of pure PTA, IPTA, TPTA and PTA–IPTA internal mixtures. Furthermore, the results generated using HAM were tested against traditional KT and FHH-AT to compare their water uptake predictive capabilities. A single hygroscopicity parameter was also developed based on the HAM framework. Results show that the HAM-based hygroscopicity parameter can successfully simulate the water uptake behavior of the pure and internally mixed samples. Results indicate that the HAM framework may be applied to atmospheric aerosols of varying chemical structures and aqueous solubility.